2020
DOI: 10.3390/molecules25153364
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Multidrug Resistance: Flavonoid and Terpenoid Nitrogen-Containing Derivatives as ABC Transporter Modulators

Abstract: Multidrug resistance (MDR) in cancer is one of the main limitations for chemotherapy success. Numerous mechanisms are behind the MDR phenomenon wherein the overexpression of the ATP-binding cassette (ABC) transporter proteins P-glycoprotein (P-gp), breast cancer resistance protein (BCRP) and multidrug resistance protein 1 (MRP1) is highlighted as a prime factor. Natural product-derived compounds are being addressed as promising ABC transporter modulators to tackle MDR. Flavonoids and terpenoids have been exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 142 publications
0
34
1
Order By: Relevance
“…ABCB1 (also known as MDR1 or P-glycoprotein) was the first ABC transporter to be identified by Ling et al and is by far the most studied MDR-related efflux pump ( Juliano and Ling, 1976 ). ABCB1 is constitutively expressed in organs and physiological barriers, including kidney, intestine, and the blood-brain barrier ( Gonçalves et al, 2020 ). It has been extensively reported that overexpression of ABCB1 in cancer cells can confer resistance to chemotherapeutic agents such as paclitaxel, vincristine, colchicine, as well as tyrosine kinase inhibitors (TKIs) such as imatinib and dasatinib ( Dohse et al, 2006 ; Hegedus et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…ABCB1 (also known as MDR1 or P-glycoprotein) was the first ABC transporter to be identified by Ling et al and is by far the most studied MDR-related efflux pump ( Juliano and Ling, 1976 ). ABCB1 is constitutively expressed in organs and physiological barriers, including kidney, intestine, and the blood-brain barrier ( Gonçalves et al, 2020 ). It has been extensively reported that overexpression of ABCB1 in cancer cells can confer resistance to chemotherapeutic agents such as paclitaxel, vincristine, colchicine, as well as tyrosine kinase inhibitors (TKIs) such as imatinib and dasatinib ( Dohse et al, 2006 ; Hegedus et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite higher safety of the new compounds, various disadvantages associated with them have been reported. Currently, there are studies focused on synthetic modifications of natural products in order to boost pharmacokinetic parameters [10][11][12][13]. At the continuous absence of ABCB1-targeted "adjuvants" in pharmaceutical market, and taking into account their potential advantages for the cancer therapy development, the search for ABCB1 modulators is still a great challenge of pharmaceutical 10.1002/cmdc.202100252…”
Section: Introductionmentioning
confidence: 99%
“…have already been reported as inhibitors of several CYP enzymes (e.g., the noncompetitive inhibition of CYP2C9 caused by genistein and daidzein [ 245 ]). Both flavonoids and terpenoids have the ability to modulate ABC transporters [ 192 , 617 ], which can be advantageous for drugs with poor absorption, but can also lead to toxic plasma drug concentrations, especially for narrow therapeutic window drugs.…”
Section: Interactions Between Botanicals and Drugsmentioning
confidence: 99%
“…have already been reported as inhibitors of several CYP enzymes (e.g., the n petitive inhibition of CYP2C9 caused by genistein and daidzein [245]). Both fla and terpenoids have the ability to modulate ABC transporters [192,617], which ca vantageous for drugs with poor absorption, but can also lead to toxic plasma dr centrations, especially for narrow therapeutic window drugs. 4, apigenin, EGCG, g hypericin, quercetin, caffeic acid, catechin, cinnamaldehyde, curcumin, delphinid olin, naringenin, puerarin, rosmarinic acid, and resveratrol show the capacity to with all nine drugs.…”
Section: Bioactivementioning
confidence: 99%